A Genetically Encoded, Phage‐Displayed Cyclic‐Peptide Library. (9th September 2019) - Wang, Xiaoshan Shayna; Chen, Peng‐Hsun Chase; Hampton, J. Trae; Tharp, Jeffery M.; Reed, Catrina A.; Das, Sukant K.; Wang, Duen‐Shian; Hayatshahi, Hamed S.; Shen, Yang; Liu, Jin; Liu, Wenshe Ray
Abstract: Superior to linear peptides in biological activities, cyclic peptides are considered to have great potential as therapeutic agents. To identify cyclic‐peptide ligands for therapeutic targets, phage‐displayed peptide libraries in which cyclization is achieved by the covalent conjugation of cysteines have been widely used. To resolve drawbacks related to cysteine conjugation, we have invented a phage‐display technique in which its displayed peptides are cyclized through a proximity‐driven Michael addition reaction between a cysteine and an amber‐codon‐encoded N ϵ ‐acryloyl‐lysine (AcrK). Using a randomized 6‐mer library in which peptides were cyclized at two ends through a cysteine–AcrK linker, we demonstrated the successful selection of potent ligands for TEV protease and HDAC8. All selected cyclic peptide ligands showed 4‐ to 6‐fold stronger affinity to their protein targets than their linear counterparts. We believe this approach will find broad applications in drug discovery. Abstract : Ein Ring, sie zu binden : Durch Unterdrückung des Amber‐Codons wurde N ϵ ‐Acryloyllysin gentechnisch in einer Phagendisplay‐Peptidbibliothek für die Cyclisierung mit zuvor eingeführtem Cystein kodiert. Selektion aus dieser Phagendisplay‐Bibliothek lieferte cyclische Peptide, die TEV‐Protease und Histon‐Deacetylayse (HDAC8) viel stärker als ihre linearen Gegenstücke binden.